Genetic variability and association analyses of morphological and biochemical traits in Tamarindus indica L. clones - A. Mayavel1*, J. Padmanaban2, A. Nicodemus1, B. Nagarajan1, C. Bagathsingh1, M. Akshayasri1, G. Radha Krishnan 1 and M. Amaravel1 (Electronic Journal of Plant Breeding)
The study aimed to investigate the genetic variability and association of morphological and biochemical characters of 60 different Tamarind clones. The experiment was conducted in 10-year-old germplasm bank of Tamarind at ICFRE-IFGTB Field Research Station, Kurumbapatti, Salem, Tamil Nadu, India. Analysis of variance revealed significant variation among clones for the morphological and biochemical characters. High phenotypic and genotypic coefficients of variation were observed for the parameters like annual yield per tree, fruit weight, pulp weight, seed weight, shell weight, vein weight, number of seeds per fruit, fruit length, fruit thickness, fruit width and total sugar content. High broad-sense heritability and high genetic advance per cent mean were recorded for annual yield per tree, tree height, number of primary branches, fruit weight, pulp weight, seed weight, shell weight, vein weight, number of seeds per fruit, fruit length, fruit thickness, fruit width, ascorbic acid, total acidity, total sugar, reducing sugar, non-reducing sugar and protein. Phenotypic path analysis highlighted positive direct effect of fruit weight, pulp weight and seed weight on annual yield per tree. Mahalanobis D-square analysis clustered the 60 tamarind clones into ten groups with higher inter-cluster distances highlighting the substantial genetic diversity present among the genetic resources. This comprehensive assessment provides insights for the genetic improvement of tamarind, aiding in the selection of superior genotypes for breeding programs.